A Metabolomic Overview of Follicular Fluid in Cows - Guerreiro, Tatiane Melina; Gonçalves, Roseli Fernandes; Melo, Carlos Fernando O. Rodrigues; de Oliveira, Diogo Noin; Lima, Estela de Oliveira; Visintin, Jose Antônio; de Achilles, Marcos Antônio; Catharino, Rodrigo Ramos (Frontiers in Veterinary Science, 2018)
Follicular fluid (FF) protects the oocyte against proteolysis and extrusion during ovulation, providing an appropriate microenvironment that favors proper embryonic development; thereby, FF plays a key role in embryo quality. Being directly related to cattle breeding, studying FF is extremely important in livestock science to measure cattle fertility. This may eventually help to assess the quality of both meat and milk, products widely consumed worldwide. There is an important commercial interest in the evaluation and characterization of compounds present in the FF of livestock that present greater likelihood of pregnancy. Mass spectrometry is a great ally for this type of analysis and can provide quick and efficient screening for molecular markers in biological samples. The present study demonstrated the potential of high-resolution mass spectrometry in analyzing FF samples from two distinct groups of Nellore cows (Bos indicus): high and low fertility, as determined by the number of oocytes produced. We were able to delineate markers of interest for each group, which may ultimately be related to biochemical pathways that lead to higher or lower reproductive performance.